Gestión de un centro de acopio y reciclaje de residuos sólidos urbanos e inclusión social de los recicladores del botadero controlado El Milagro, Trujillo 2014. - Tincopa Agreda, Stephany Genesis (2014)
The present investigation is aimed at determining how the management of a collecting and recycling center of municipal solid waste promotes social inclusion of recyclers from the Controlled Landfill El Milagro. These recyclers have being one of the most affected minorities of recycling activity in the province of Trujillo. The hypothesis stated in this study is that the management of a collecting and recycling center of municipal solid waste can effectively promote the social inclusion of recyclers at the Controlled Landfill El Milagro. For this purpose, two samples were taken as objects of study. The first sample was taken from the group of recyclers at The Controlled Landfill El Milagro and the second, from the recyclers included in the segregation program of SEGAT (Environmental Management Service of Trujillo). A survey was applied as a tool for collecting information about the presence of social inclusion in the two different samples. The questions were formulated considering some of the main elements of social inclusion. The conclusion was that the management of a center for collection and recycling of municipal solid waste; through good work conditions, training, strengthening identity and high motivation of workers , can promote the social inclusion of informal recyclers at The Cotrolled Landfill El Milagro.